2021
DOI: 10.21203/rs.3.rs-146042/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors for Poor Health-related Quality of Life in Patients With Colon Cancer Include Stoma and Smoking Habits

Abstract: Objectives: Studies have shown that poor Health-related quality of life (HRQoL) might worsen the cancer-related prognosis. The aim of this study was to investigate risk factors for poor HRQoL in patients with colon cancer.Method: This was a prospective population-based study of patients with colon cancer included between 2012 and 2016. HRQoL was measured using the cancer-specific European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C30. Multiple linear regression analysis ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…No randomized controlled studies were identified. The studies originated from Spain, 32 Germany, 20,24,27,33 USA, 22,28,29,34–36 China, 37,38 Italy, 21 Sweden, 23,39 the United Kingdom, 25,26,40 the Netherlands, 31,41,42 New Zealand, 30 Denmark, 43 and Canada 44 . In total 6972 participants were included.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No randomized controlled studies were identified. The studies originated from Spain, 32 Germany, 20,24,27,33 USA, 22,28,29,34–36 China, 37,38 Italy, 21 Sweden, 23,39 the United Kingdom, 25,26,40 the Netherlands, 31,41,42 New Zealand, 30 Denmark, 43 and Canada 44 . In total 6972 participants were included.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐four (96%) of the studies had good selection, and 12 studies (48%) were assessed as having good comparability using the Newcastle‐Ottawa Scale assessment tool (Table S5). Thirteen of the twenty‐five studies (52%) exhibited a study level “good” quality assessment, 21–23,27–30,32,33,37,41–43 eight (32%) “fair” quality, 20,25,31,35,38–40,44 and four (20%) “unclear” quality, 24,26,34,36 and none of the included studies were found to be of “poor” quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations